The Changing Roles of Ulama and the Evolution of Islamic Schools: Some Insights from Moroccan and Indonesian Cases - Auliya Ridwan (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2022)
The ulama, who are scholars in the Islamic tradition, play a vital role in preserving the prophet's teachings and passing them down to future generations. In addition to this, they also have other important social functions. The combination of religious and social roles within the ulama allows them to influence social change with religious legitimacy. This article explores how the social roles of the ulama have evolved over time and how this has impacted the existence of Islamic schools. To illustrate this, examples are drawn from the literature on Morocco and Indonesia during the 20th and 21st centuries. During the colonial period in Morocco, the ulama and Islamic schools served as a cultural defense against French colonial influence. Meanwhile, in Indonesia, Islamic schools led by Ulama became the foundation of the Muslim resistance movement against Dutch colonial rule. In both cases, Islamic scholars and schools demonstrated their ability to respond to actual social situations, highlighting their cultural power and importance in society.